Body biographies: a study of apprenticeship and embodied experience among tattoo artists in Mexico - González Varela, Sergio (LUD. Organ Polskiego Towarzystwa Ludoznawczego, 2023)
Based on the author’s long-term fieldwork experience in Mexico, this article describes the apprenticeship experience of tattoo artists. It deals with the learning process of a craft, how artists develop skills and techniques, and how they share their knowledge with others. The text argues that the solidarity that the tattoo community creates passes not only through the relationship between artists and clients but also through the exchange and reciprocity between professionals through the mutual inking of their bodies, in what the author calls body biographies. The article also depicts the importance of social media in promoting an artist’s work and how a person becomes an expert or a professional. Finally, it analyzes the growing popularity of tattoos and the saturated market it creates, where artists compete for clients, prestige, and money.